Brown‑Sequard Syndrome: A Case Series from a Regional Hospital in Nigeria - Toluse, Adetunji; Adeyemi, Taofeek; Angaye, Ebikiye; Alimi, Mustapha (Nigerian Journal of Orthopaedics and Trauma, 2020)
Brown‑Sequard syndrome (BSS) is the constellation of symptoms and signs following hemisection or hemicompression of the spinal cord. The syndrome is an uncommon form of incomplete spinal cord injury with clinical presentation of ipsilateral motor weakness, impaired proprioception and vibratory sensation, with contralateral loss of pain and temperature sensation below the level of the lesion. We report two cases of BSS following penetrating (stab) injuries. The patients were managed non‑operatively and they were followed up for 12 and 18 months, respectively, during which they made significant neurologic recovery on the Medical Research Council scale. The objective of this report is to highlight that BSS following trauma can be managed non‑operatively with good neurologic outcome in cases where there is no extrinsic compression of the neural tissues.